ANALYSIS OF THE IMPLEMENTATION OF COMMUNITY-BASED TOURISM IN SUPPORTING HALAL TOURISM IN NORTH LOMBOK REGENCY: ANALYSIS OF THE IMPLEMENTATION OF COMMUNITY-BASED TOURISM IN SUPPORTING HALAL TOURISM IN NORTH LOMBOK REGENCY - Abdurrahman, Abdurrahman; Mujahid Dakwah, Muhammad; Najib Roodhi, Mohammad; Handayani Rinuastuti, Baiq; Pahrudin, Pahrudin (Journal of Institution and Sharia Finance, 2024)
This study aims to analyze the application of community-based tourism in supporting the development of halal tourism in North Lombok. The research method used is a qualitative method with a case study approach. Data collection was carried out through in-depth interviews, observations, and documentation studies. The results of the study show that the implementation of community-based tourism has had a positive impact on the development of halal tourism in North Lombok. The local community is actively involved in the planning, management, and supervision of tourist destinations, so that they can meet the needs and preferences of Muslim tourists. In addition, community-based tourism has also improved the economic welfare of local communities through business opportunities and employment in the tourism sector. However, there are still several challenges in the implementation of community-based tourism, such as limited resources, coordination between stakeholders (local governments), and the capacity of local communities. Therefore, more comprehensive efforts are needed to optimize the implementation of community-based tourism in supporting the development of halal tourism in North Lombok.